2004
DOI: 10.1210/en.2003-1271
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Agonists Reverse the Molecular Defects Associated with Dominant-Negative Mutations in Human Peroxisome Proliferator-Activated Receptor γ

Abstract: Loss-of-function mutations in the ligand-binding domain of human peroxisome proliferator-activated receptor gamma (PPARgamma) are associated with a novel syndrome characterized by partial lipodystrophy and severe insulin resistance. Here we have further characterized the properties of natural dominant-negative PPARgamma mutants (P467L, V290M) and evaluated the efficacy of putative natural ligands and synthetic thiazolidinedione (TZD) or tyrosine-based (TA) receptor agonists in rescuing mutant receptor function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…A number of diseases are associated with mutations in NR genes, frequently affecting the LBD (57,58). In some cases, the functional defect can be (partially) rescued by specific ligands as exemplified by the effects of synthetic tyrosinebased agonists on the FPLD3-associated PPAR␥ V318M and P495L mutants (59). Characterization of NR mutants using NR-coregulator interaction profiling can therefore provide the rationale for therapy in such cases.…”
Section: Figmentioning
confidence: 99%
“…A number of diseases are associated with mutations in NR genes, frequently affecting the LBD (57,58). In some cases, the functional defect can be (partially) rescued by specific ligands as exemplified by the effects of synthetic tyrosinebased agonists on the FPLD3-associated PPAR␥ V318M and P495L mutants (59). Characterization of NR mutants using NR-coregulator interaction profiling can therefore provide the rationale for therapy in such cases.…”
Section: Figmentioning
confidence: 99%
“…In vitro studies of both mutations suggest a destabilization of the PPARg configuration more favorable for receptor-corepressor interactions with dominant-negative properties. Interestingly, a PPARg ligand stabilizes the receptor structure in the active conformation and promotes co-repressor release, which most likely explains the improvement of these patients' condition after TZD treatment [192].…”
Section: Pparg Loss Of Function Mutationsmentioning
confidence: 99%
“…In 293EBNA cells without the addition of an exogenous ligand, PPARG did not exhibit silencing function but rather constitutive activation of basal transcription (Barroso et al 1999, Agostini et al 2004, Semple et al 2006. Additionally, overexpression of NCoR did not potentiate the suppression by PPARG2 of acyl-CoA oxidase-derived PPRE (Aox-PPRE) in 293T cells (Zamir et al 1997).…”
Section: Introductionmentioning
confidence: 95%
“…Barroso et al (1999) and Savage et al (2003) reported two different heterozygous mutations, PPARG1-P467L and V290M, in patients with severe insulin resistance. Both mutants, PPARG1-P467L in particular, have very low affinity for the PPARG ligands and constitutively bind with CoR (Barroso et al 1999, Agostini et al 2004. They are believed to be resistant to the endogenous ligand since they exhibited no transactivation in 293EBNA cells in the absence of an exogenous ligand (Barroso et al 1999, Agostini et al 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation